Light scattering on PHA granules protects bacterial cells against the harmful effects of UV radiation - Slaninova, Eva; Sedlacek, Petr; Mravec, Filip; Mullerova, Lucie; Samek, Ota; Koller, Martin; Hesko, Ondrej; Kucera, Dan; Marova, Ivana; Obruca, Stanislav (Applied microbiology and biotechnology, 2018)
Numerous prokaryotes accumulate polyhydroxyalkanoates (PHA) in the form of intracellular granules. The primary function of PHA is the storage of carbon and energy. Nevertheless, there are numerous reports that the presence of PHA granules in microbial cells enhances their stress resistance and fitness when exposed to various stress factors. In this work, we studied the protective mechanism of PHA granules against UV irradiation employing Cupriavidus necator as a model bacterial strain. The PHA-accumulating wild type strain showed substantially higher UV radiation resistance than the PHA non-accumulating mutant. Furthermore, the differences in UV-Vis radiation interactions with both cell types were studied using various spectroscopic approaches (turbidimetry, absorption spectroscopy, and nephelometry). Our results clearly demonstrate that intracellular PHA granules efficiently scatter UV radiation, which provides a substantial UV-protective effect for bacterial cells and, moreover, decreases the intracellular level of reactive oxygen species in UV-challenged cells. The protective properties of the PHA granules are enhanced by the fact that granules specifically bind to DNA, which in turn provides shield-like protection of DNA as the most UV-sensitive molecule. To conclude, the UV-protective action of PHA granules adds considerable value to their primary storage function, which can be beneficial in numerous environments.
Keywords: reaktivní formy kyslíku; UV radiation; DNA, Bacterial; Ultraviolet Rays; Cupriavidus necator; mikrobiální viabilita; polyhydroxyalkanoáty; Microbial Viability; Polyhydroxyalkanoates; Reactive Oxygen Species; Integrating sphere; Turbidity; DNA bakterií; ultrafialové záření; Nephelometry